THARIQAH NUUR AL-BAYAAN FII TA'LIMIL LUGHOH 'ARABIYAH - Bahruddin, Uril (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2010)
There have been many efforts of developing Arabic learning either in Arab countries and other countries, including Indonesia. Some of the methods developed are the â€œtarjamahâ€ method, direct method, listening and speaking method as well as communicative methods. All the methods are aimed at the effective ways of learning Arabic. One of the new methods developed by Muhammad Dawud, a director of the Institute of Al-Quran Teacher Education in Cairo Egypt is called the method of Nurul Bayan. This method emphasizes the closeness and interaction between an Arabic learner and Al-Quran that is an example of the most perfect Arabic.